Dr. Luis Sanchez, Julianne Gavino, Yosduan Ramos at 2017 SURF Program Reception
Assistant Professor of Sociology, Dr. Luis Sanchez; Julianne Gavino Lecturer of Art; and CSUCI student Yosduan Ramos at 2017 SURF Program Reception.